Nutritional status of people experiencing homelessness: Scoping review protocol (Research, Society and Development, 2024)
The present study is a scoping review protocol whose objective is to identify and map the existing scientific production on the nutritional status of people experiencing homelessness. This protocol will follow the methodological steps proposed by the Joana Briggs Institute (JBI) Manual for Evidence Synthesis and was prepared in accordance with the PRISMA-ScR Checklist and Explanation. The search for studies of interest will be carried out in the databases PubMed, Lilacs, EMBASE, Scopus, Web of science, CINHAL, PsycINFO and JSTOR and the investigation of gray literature will initially take place using Google Scholar. The findings will be exported to the EndNote reference manager and, later, to the Rayyan Software where the selection of studies will be carried out - by two independent reviewers -, according to the inclusion criteria. Data will be extracted using a form developed by the authors and will be displayed using tables and/or charts and analyzed in a descriptive way. From the mapping of what currently exists in the scientific literature on the nutritional status of the homeless population, the aim is to synthesize such knowledge and give visibility to the issues of this population, enabling future research on this topic.